![image](https://tex.z-dn.net/?f=+%5Csqrt%7Bx%5E2%2B8%7D%2B%5Csqrt%7Bx%5E2-1%7D%3D4-x%5E2%5C%5C%0A+x%5E2-1%3Dt%5E2%5C%5C%0A%5Csqrt%7Bt%5E2%2B9%7D%2B%5Csqrt%7Bt%5E2%7D%3D3-t%5E2%5C%5C+%0At%3E0%5C%5C%0A%283-t%5E2-t%29%5E2-t%5E2-9%3D0%5C%5C%0At%28t%5E3%2B2t%5E2-6t-6%29%3D0%5C%5C%0At%3D0%5C%5C%0At%5E2+%5Cleq+3%5C%5C%0A%0A+)
0\\
(3-t^2-t)^2-t^2-9=0\\
t(t^3+2t^2-6t-6)=0\\
t=0\\
t^2 \leq 3\\
" alt=" \sqrt{x^2+8}+\sqrt{x^2-1}=4-x^2\\
x^2-1=t^2\\
\sqrt{t^2+9}+\sqrt{t^2}=3-t^2\\
t>0\\
(3-t^2-t)^2-t^2-9=0\\
t(t^3+2t^2-6t-6)=0\\
t=0\\
t^2 \leq 3\\
" align="absmiddle" class="latex-formula">
корни второго уравнения , по графику , видно не имеют подходящего корня
откуда следует